2004
DOI: 10.1074/jbc.m402088200
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Therapeutic Angiogenesis Using Genetically Modified Human Endothelial Progenitor Cells with Altered Glycogen Synthase Kinase-3β Activity

Abstract: Previously we reported that inhibition of glycogen synthase kinase-3␤ (GSK3␤), a key regulator in many intracellular signaling pathways, enhances the survival and migration of vascular endothelial cells. Here we investigated the effect of inhibition of GSK3␤ activity on the angiogenic function of endothelial progenitor cell (EPC) and demonstrated a new therapeutic angiogenesis strategy using genetically modified EPC. As we previously reported, two biologically distinct types of EPC, spindle-shaped "early EPC" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 42 publications
1
60
0
2
Order By: Relevance
“…17 HUVECs (4ϫ10 4 cells) suspended in 1 mL of Medium-199 containing 2% fetal bovine serum with control saline or with different concentrations of rhG-CSF (1, 10, and 100 ng/mL) were cultured on growth factor-reduced Matrigel (Becton Dickinson, San Jose, Calif). After a 12-hour incubation period at 37°C under 5% CO 2 within humidified atmosphere, endothelial network formation was examined and photographed at randomly chosen fields in each well (ϫ40).…”
Section: In Vitro Angiogenesis Model: Endothelial Network Formation Omentioning
confidence: 99%
“…17 HUVECs (4ϫ10 4 cells) suspended in 1 mL of Medium-199 containing 2% fetal bovine serum with control saline or with different concentrations of rhG-CSF (1, 10, and 100 ng/mL) were cultured on growth factor-reduced Matrigel (Becton Dickinson, San Jose, Calif). After a 12-hour incubation period at 37°C under 5% CO 2 within humidified atmosphere, endothelial network formation was examined and photographed at randomly chosen fields in each well (ϫ40).…”
Section: In Vitro Angiogenesis Model: Endothelial Network Formation Omentioning
confidence: 99%
“…Ainsi, l'inhibition de la GSK3 (glycogen synthase kinase 3) augmente la sécrétion de VEGF et d'interleukine-8, la survie et la prolifération des CPE précoces et la survie et la différenciation des CPE tardives [35]. La plupart des facteurs de risque cardiovasculaire inhibent la fonction des cellules souches/progénitrices.…”
Section: Modifications Génétiquesunclassified
“…Recently, it has been proposed that genetic engineering of EPC aimed at increasing the production of growth factors, promoting their cytoprotective properties or extending their life span is an effective procedure to improve the curative effects of EPC. 58 Choi et al 59 showed that inhibition of glycogen synthase kinase-3b (GSK3b) signaling pathway led to increased nuclear translocation of b-catenin and increased secretion of angiogenic cytokines (VEGF and IL-8). It enhanced the survival and proliferation of early EPC, whereas it promoted the survival and differentiation of late EPC.…”
Section: Bone Marrow-derived Endothelial Progenitor Cells As Carriersmentioning
confidence: 99%
“…Transplantation of either of these genetically modified EPC into the ischemic hindlimb model of athymic nude mouse significantly improved blood flow, limb salvage and tissue capillary density compared with nontransduced EPC. 59 In an animal model of experimentally induced limb ischemia, Iwaguro el al. 60 showed that administration of EPC transduced with adenovirus encoding VEGF improved neovascularization and blood flow recovery and reduced amputation rate.…”
Section: Bone Marrow-derived Endothelial Progenitor Cells As Carriersmentioning
confidence: 99%